Beam Dynamics Investigation for the Compact Seeded THz-FEL Amplifier - S. Suphakul (2018)
© 2016 Published by Elsevier Ltd. A compact seeded terahertz (THz) free-electron laser (FEL) amplifier is under development at the Institute of Advanced Energy, Kyoto University. The system consists of a 1.6-cell S-band BNL-type photocathode radio frequency (RF) gun, a focusing solenoid magnet, a magnetic bunch compressor, focusing quadrupoles, a short planar undulator and a THz parametric generator for seeding. The accelerator system will generate a high brightness ultra-short electron bunch injected to the short undulator. Since characteristics of the emitted radiation strongly depend on the electron beam properties, the beam dynamics of the system has been investigated. As the result, the system should be operated at the high accelerating voltage of 80 MV/m to avoid the space-charge effect which causes serious bunch lengthening. The laser with the uniform temporal distribution and the injection phase of 12 degree is suitable for the bunch compression in the chicane. This condition provides the electron beam injected to the undulator with the peak current of more than 300 A and the FWHM bunch length of 0.36 ps at the bunch charge of 200 pC.